Ecological functional zoning for mineral resource development in Xizang, China - Xiangying Jia; Chonghao Liu; Jing Liu; Jianan Zhao; Xiu Wang; Niannian Li; Tianjiao Li (PLoS ONE, 2025)
Xizang is an important base of mineral resources, hosting abundant deposits. However, its unique and fragile ecological environment has long constrained resource development and utilization. Achieving a balance between ecological protection and mineral resource exploitation has become a pressing issue. This study proposes a novel approach for ecological functional zoning to provide scientific evidence for mineral resource development in Xizang. The study employs remote sensing image interpretation and single-factor ecological indicators analysis to construct a comprehensive ecological environment assessment system, scientifically delineating ecological function zoning for mineral resource development in Xizang. The results indicate that Xizang can be divided into five functional zones: (I) Northern Plateau Desert Zone, (II) Plateau Grassland Zone, (III) Plateau Mountain Zone, (IV) High Mountain-Forest Zone, and (V) Eastern Canyon Zone. Zone I and Zone III exhibit relatively favorable conditions for development but also face significant ecological vulnerability. Therefore, development activities in these areas must be rigorously controlled to minimize environmental disturbances. Zone II and Zone IV impose substantial constraints on resource development due to the heightened sensitivity of their ecosystems, necessitating stringent conservation measures. While Zone V demonstrates strong ecological restoration capabilities, it remains highly susceptible to water resource contamination and soil erosion risks. The innovative outcomes of this study lie in integrating comprehensive regional zoning and quantitative ecological environment assessments, providing an actionable framework for the coordinated development of mineral resources and ecological protection, thus advancing the scientific and refined management of resources and the environment.